Middle Years of Marriage: Love and Marital Satisfaction Among Wives - Firza Ersalina Prasetyo; Sri Wahyuningsih; Nurlita Endah Karunia (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
In the middle years of marriage, marital satisfaction tends to decline, particularly among wives because of their caregiving roles for children and parents (transgenerational squeeze), and because their husbands focus more on their work. This may weaken love despite that love can provide happiness and lead to marital satisfaction. This study examined the relationships between love and marital satisfaction and determined which components of love that had the highest correlation with marital satisfaction. Data collected using questionnaires. Results showed that love had a positive relationship with wives’ marital satisfaction in the middle years of marriage (p < .001). The components of love having significant relationships with marital satisfaction from the highest to the lowest correlation were intimacy, commitment, and passion.